The shark-toothed dolphin Squalodon (Cetacea: Odontoceti) from the remarkable Montagna della Majella marine vertebrate assemblage (Bolognano Formation, central Italy) - Collareta, Alberto; Di Cencio, Andrea; Ricci, Renato; Bianucci, Giovanni (Association "Carnets de Géologie", 2020)
The extinct family Squalodontidae consists of heterodont, medium-sized odontocetes, featuring a long rostrum that houses large, procumbent incisors and heavily ornamented postcanine teeth carrying accessory denticles, hence their vernacular name, "shark-toothed dolphins". These longirostrine toothed whales are often seen as bridging the anatomical gap between archaic Oligocene odontocetes and their late Miocene to Holocene relatives. Possibly among the major marine predators of their time, the shark-toothed dolphins are important components of several lower Miocene marine-mammal assemblages from the North Atlantic and Mediterranean/Paratethysian realms. In the present work, a partial skull of Squalodontidae is described from the strata of the Bolognano Formation cropping out in the northeastern sector of the Montagna della Majella massif (Abruzzo, central Italy), which has previously yielded a rich lower Miocene marine-vertebrate assemblage, including eleven taxa of elasmobranchs as well as subordinate teleosts and very fragmentary remains of marine reptiles and mammals. The specimen consists of the anterodorsal portion of a rostrum, preserving parts of both premaxillae and left maxilla, and the anteriormost seven upper left teeth. This partial skull is here identified as belonging to the genus Squalodon, whose presence in the Montagna della Majella vertebrate assemblage had already been tentatively proposed on the basis of two fragmentary teeth. The paleontological significance of this find is discussed in the broader framework of the Euromediterranean record of Squalodon. La famille éteinte des Squalodontidae comprend des odontocètes de taille moyenne, hétérodontes, présentant un long rostre qui abrite de grandes dents incisives procombantes et de post-canines très ornées comportant des denticules accessoires, d'où leur nom vernaculaire "dauphins à dents de requin". Ces odontocètes longirostres sont souvent perçus comme des formes intermédiaires comblant le fossé anatomique entre les odontocètes oligocènes ...